2011
DOI: 10.4236/eng.2011.35058
|View full text |Cite
|
Sign up to set email alerts
|

Gas Turbine Performance Optimization Using Compressor Online Water Washing Technique

Abstract: The ability to predict the behaviour of a gas turbine engine and optimize its performance is critical in eco-nomic, thermal and condition monitoring studies. Having identified fouling as one of the major sources of compressor and therefore gas turbine deterioration, a computer-based engine model was developed to optimize the performance of gas turbines. The paper thus presents an analysis of compressor hand cleaning, on and offline compressor washing to actualize the technique using a computer program in Visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“… The research by Ogbonnaya (2011) showed that the compressor efficiency and the overall operational efficiency were improved to 82 percent and 45.8 percent with optimized online water-washing. However, frequent compressor blade washing behaviors can increase the operational and maintenance (O&M) costs.…”
Section: Introductionmentioning
confidence: 99%
“… The research by Ogbonnaya (2011) showed that the compressor efficiency and the overall operational efficiency were improved to 82 percent and 45.8 percent with optimized online water-washing. However, frequent compressor blade washing behaviors can increase the operational and maintenance (O&M) costs.…”
Section: Introductionmentioning
confidence: 99%
“…It mainly includes: compressor corrosion and blade washing [2][3], modelling and optimization of multiphase flow in online washing [4] as well as the analysis of the effect of washing on engine performance [5][6] and so on. Domestic research on washing technology has just started and mainly focuses on shore-based aero engines.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental setup to actualize the optimization technique is shown in figure 3. The turbotech equipment is manually operated using a hand pump that injects the deminerialized water (Ogbonnaya, 2011). Equation (10) was used in developing a software, code named the VANCANAL, written in figure 4.…”
Section: The Optimization Techniquesmentioning
confidence: 99%
“…With increasing operating time, degradation of compressors manifest in the form of reduced performance. The major cause of reduction in compressor efficiency and inlet air mass flow is fouling (Ogbonnaya, 2011). Other forms of site conditions are abrasion and erosion of the blade surfaces.…”
Section: Introductionmentioning
confidence: 99%